Constant pressure filtration of sugar beet pulp-ammonium oxalate solution mixtures - Kar, F (Int Sugar Journal Ltd, 2000)
Sugar beet pulp-ammonium oxalate solution mixtures were vacuum filtered at 25 degrees C filtration temperature and different filtration pressures (0.13 x 15(0) Pa, 0.20 x 10(5) Pa, 0.27 x 10(5); Pa) and the cake compressibility coefficient was calculated at 25 degrees C as 0.903. Specific cake resistance was dependent on the filtration pressure. The correlation between the filtration pressure and the average specific cake resistance showed that sugar beet pulp-ammonium oxalate solution mixture forms compressible filter cake. The effects of the precoating amount and filter aid dose on specific cake resistance were investigated using peanut peel as a filter aid to increase the filtration efficiency. Compared to experiments without filter aid, specific cake resistance decreased with filter aid dose.
Keywords: Pectin